1981
DOI: 10.3382/ps.0601415
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Dietary and Intravenously Administered Moniliformin to Broiler Chickens

Abstract: Moniliformin (1-hydroxy-cyclobut-1-ene-3,4-dione), either purified (0, 8, and 16 mg/kg of diet) or from culture of Fusarium moniliforme strain NRRL 6322 on corn grits (8, 16, and 64 mg/kg of diet) was fed to growing broiler chicks from 1 to 21 days of age. Up to 16 mg moniliformin/kg of diet from either source was without effect on chick weight gain, feed consumption, and mortality. Chicks fed 64 mg moniliformin/kg of diet from culture had reduced weight gain and feed consumption. Total daily moniliformin cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
3
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 8 publications
0
24
3
1
Order By: Relevance
“…Initial studies of moniliformin toxicity in poultry involved determination of median lethal dose (LD 50 ) values in chickens (Burmeister et al, 1979;Kriek et al, 1977). Allen et al (1981) fed chicks purified M or M supplied by culture material at levels ranging from 8 to 64 mg/kg and observed reduced performance and 15% mortality in chicks fed 64 mg M/kg for 3 weeks. Ledoux et al (1995) demonstrated that 50 mg M/kg or greater is toxic to broiler chickens with mild to severe cardiomegaly observed in chickens fed 50 to 200 mg M/kg ration.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of moniliformin toxicity in poultry involved determination of median lethal dose (LD 50 ) values in chickens (Burmeister et al, 1979;Kriek et al, 1977). Allen et al (1981) fed chicks purified M or M supplied by culture material at levels ranging from 8 to 64 mg/kg and observed reduced performance and 15% mortality in chicks fed 64 mg M/kg for 3 weeks. Ledoux et al (1995) demonstrated that 50 mg M/kg or greater is toxic to broiler chickens with mild to severe cardiomegaly observed in chickens fed 50 to 200 mg M/kg ration.…”
Section: Introductionmentioning
confidence: 99%
“…Fusaproliferin can induce teratogenic effects, e.g., cephalic dichotomy, macrocephaly, and limb asymmetry, in chicken embryos (26). Moniliformin is a sodium or potassium salt of 1-hydroxycyclobut-1-ene-3,4-dione (4,24), which has been shown to be extremely toxic to animals such as ducklings, rats, mice, chickens, and swine (1,2,13).…”
mentioning
confidence: 99%
“…MON has not been involved in any natural animal or human disease outbreaks, but has shown comparable toxicity to the most toxic trichothecenes, T-2 toxin and HT-2 toxin, in laboratory experiments involving birds and rodents (Abbas et al, 1990;Allen et al, 1981;Burmeister et al, 1979;Kriek et al, 1977;Nagaraj et al, 1996;Ueno, 1983).…”
Section: Introductionmentioning
confidence: 93%